The Impact of Shareholder Litigation Risk on Equity Incentives: Evidence from a Quasi-Natural Experiment - Yang, Jingyu; Yu, Yangxin; Zheng, Liu (The Accounting Review, 2021)
ABSTRACT While prior studies generally support that equity-based compensation induces CEOs to manipulate financial reporting, there is limited direct empirical evidence on whether financial misreporting concerns affect compensation design. A key challenge for establishing a causal relationship is that misreporting incentives and compensation policies are often endogenously determined. Exploiting the exogenous reduction in litigation threat following a 1999 ruling of the U.S. Ninth Circuit Court of Appeals, we examine how heightened misreporting concerns in a less litigious environment affect CEOs' compensation design. Consistent with the theoretical prediction that misreporting concerns prevent companies from providing more powerful incentive pay that is otherwise optimal, we find that firms headquartered in Ninth Circuit states decreased CEOs' equity portfolio vega relative to the control firms after the ruling. We further document that this reduction was concentrated among firms facing greater misreporting concerns post-ruling. JEL Classifications: J33; K22; M52.